Systematic bioinformatics analysis reveals the role of shikonin in blocking colon cancer progression by identifying senescence-induced genes - Liu, Wenna; Zhao, Yujia; Liu, Qingqing; Wu, Dan; Li, Wenxuan; Fu, Zhenkai; Yang, Le; Liang, Ying (Frontiers in Pharmacology, 2024)
Shikonin, a naturally occurring naphthoquinone compound extracted from comfrey plants, has antitumor, anti-inflammatory, and antimicrobial properties. Cell senescence plays a key role in preventing tumor progression. It is unclear whether shikonin has an effect on cell senescence in colon cancer. In the current study, we firstly determine the IC50 values of shikonin on colon cancer cell lines HT29 and HCT116, respectivelywere cultured with different concentrations of shikonin (0 μM, 6 μM, 12 μM, 24 μM, and 48 μM for HT29 cells, and 0 μM, 0.3 μM, 0.9 μM, 2.7 μM, and 8.1 μM for HCT116 cells) for 24 h. Then, wWe verified the inhibitory effects of shikonin on the proliferation and migration abilities of colon cancer cell lines HT29 and HCT116 using cell proliferationcounting kit-8, colony formation, and wound healing assays. Next, we identified a series of potential targets using highthroughput mRNA sequencing, and identified 210 upregulated and 296 downregulated genes. KEGG profiling revealed that eight downregulated genes associated with cell senescence: CCNB3, IL-1α, CXCL8, CDKN2A, MYC, IGFBP3, SQSTM1 and GADD45G. CXCL8 and CDKN2A were associated with poor prognosis in patients with colon cancer, suggesting that their downregulation by shikonin could improve patient survival. Furthermore, SA-β-galactosidase staining revealed that the percentage of cellular senescence in colon cancer cells was significantly increased after shikonin treatment. Molecular docking revealed that shikonin suppressed colon cancer progression by blocking CXCL8 activity. Based on these findings, we deem that Sshikonin might induce senescence and exert antitumor activity in colon cancer cells by downregulating CDKN2A and CXCL8. This provides a new molecular mechanism and potential therapeutic target for shikonin to inhibit colon cancer progression.